Adaptation to genome decay in the structure of the smallest eukaryotic ribosome - David Nicholson; Marco Salamina; Johan Panek; Karla Helena-Bueno; Charlotte R. Brown; Robert P. Hirt; Neil A. Ranson; Sergey V. Melnikov (Nature Communications, 2022)
Many parasitic organisms contain molecular structures that are drastically smaller than analogous structures in non-parasitic organisms. Here the authors describe a cryo-EM structure of the ribosome from E. cuniculi that reveals that it compensated rRNA truncations by evolving the ability to use small molecules as ribosomal building blocks.